Serumleptin, Triglycerides, Cholestrol and Hdl- Cholestrol In Non Dlabetic Obese Subjects - Kassim, M.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
This study was carried out to investigate the relationship between Serum leptin, Body Mass Index (BMI), Triglycerides, Cholesterol and HDL- Cholesterol in Non Diabetic Obese subjects comparing with healthy subject. A 36 male and female Iraqis obese were studied, mean age 50.1, 43.3 years respectively and 23 healthy subjects. Serum leptin, Triglycerides, Cholesterol and HDL- Cholesterol were measured. Leptin, Triglycerides, Cholesterol, HDL- Cholesterol and BMI significantly increased in obese males and females compared with control, but there was no significant difference in HDL- Cholesterol and BMI when compared between obese males and females. A low significant positive correlation was found between leptin and HDL- Cholesterol, and no significant difference between leptin and other types of lipids. The findings suggested that serum leptin concentration topmost in obese subjects with noticeable effect on lipid metabolism.